University education and levels of social competence in tourism and recreation students - Alejziak, Bożena (Turyzm/Tourism, 2020)
Social competences are one of the most important areas of an individual’s functioning in the surrounding environment. They are so important that, apart from knowledge and skills, they have become one of higher education’s outcomes. The level of social competence depends not only on the internal qualities of an individual but also on environmental factors. This article aims to present the findings of research concerning the level of social competences attained by students of tourism and recreation throughout their higher education and comprises quantitative and qualitative research methods. The results indicate that students show only average levels of social competence even though their academic teachers declare that education outcomes have been accomplished in this field.